ANALISIS KEMAMPUAN PEMECAHAN MASALAH PADA MATERI SPLDV TINGKAT SMP DITINJAU PADA GAYA BELAJAR - Nur Syifa Fauziah; Meyta Dwi Kurniasih (Prodi Pendidikan Matematika FKIP Universitas Madura, 2022)
This study uses a qualitative approach. This study aims to explain SPLDV and describe problem solving abilities that pay attention to student learning styles. The subjects used were 116 students of class VIII SMP NEGERI 10 JAKARTA selected, where later there would be 9 students who were selected according to their learning styles and descriptions of the steps for solving problems with the polya stages. Researchers collected data in the form of questionnaires, tests and interview guidelines. Based on the results of the research, the following conclusions can be drawn: 1) The ability to solve mathematical problems by teaching Poly steps allows students to understand problems, plan problem solving, and implement problem solving plans. 2) Students' mathematical problem solving abilities with auditory learning style according to Polya's stages are able to understand problems, develop problem solving plans, implement problem solving plans, and review problem solving results; 3) Mathematical problem solving ability A student with a kinesthetic learning style according to a kinesthetic learning style has a higher problem understanding and poor ability to carry out problem solving plans in terms of his ability to perform calculations according to the formula used. Mainly used for addition, multiplication, and division. Ability to review learning styles from problem solving results.